Analisis Tingkat Kepuasan Pelanggan Pada Pelayanan Lahan Parkir Menggunakan Metode Service Quality - Dwiyanto Kuncoro; Ridwan Abimanyu; Ridwan Kurniawan; Khaerul Umam (LPPM Universitas Bina Sarana Informatika, 2022)
This research was conducted to provide an assessment by observing the services and facilities applied to the campus parking lot at one of the universities. To support this research, we also collected data by distributing questionnaires to the parking lot users. In conducting the assessment, we use the Service Quality method which refers to five kinds of satisfaction attribute methods, namely reliability, responsiveness, tangible, assurance, and empathy. The assessment will be grouped based on these five kinds of attributes and the difference or distance between reality and expectations from the level of satisfaction, if the distance between reality and expectations is getting closer, the level of customer satisfaction will be higher, on the contrary if the distance between the two is getting further, the level of satisfaction will be lower. In these observations, we obtained some data and conclusions where the lowest level of satisfaction was found in the assurance assessment section, which means that the form of accountability applied to the parking lot service is still relatively low and still needs to be improved. The advice we give is to change the policy so that the form of responsibility that is applied can be improved, such as applying a warranty in the event of a loss of either the vehicle or driving equipment or conducting a search and repair in the event of loss or damage to either the vehicle or driving equipment.